Brahms and his world - Frisch, Walter, 1951-; Karnes, Kevin, 1972- (Bard Music Festival series., 2009)
A key collection of essays for listeners, performers, and scholars interested in Brahm's life, work, and times on the occasion of a music festival held at Bard College, August 1990.